Survivability Modelling of Lithuanian Government Information System - Paulauskas, N.; Garsva, E.; Gulbinovic, L.; Stankevicius, A.; Poviliauskas, D. (Elektronika ir Elektrotechnika, 2012)
This paper presents a new approach which allows us to find the system compromise probabilities and applying them to simulate computer system survivability. Also, four computer system survivability simulation models were composed and according to requirements for recovery time and accessibility of Lithuanian government information systems computer system survivability simulations were performed. Simulation models were composed using Stochastic Activity Network (SAN) formalism. Presented model allows evaluating system survivability based on threat type, incident severity and the amount of implemented security mechanisms. The model is flexible, expandable and can be adapted to other computer systems. Ill. 3, bibl. 8, tabl. 1 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.120.4.1463